EFFECT OF PERCEPTION OF PATIENT SAFETY CULTURE DIMENSIONS ON THE WILLINGNESS TO REPORT PATIENT SAFETY INCIDENT - Putri, Ekowati Supartinah Kamandaka; Nuswantari, Asih Trirachmi; Imam, Cecilia Widijati (Universitas Brawijaya, Indonesia, 2018)
The purpose of this study was to determine the effect of the perception of patient safety culture dimensions on the willingness to report patient safety incident patient safety incident. This study used a quantitative correlation design with cross-sectional approach. Data analysis used multiple linear regressions. The result showed that perception of patient safety culture dimensions simultaneously affects the willingness to report patient safety incident in Hospital X Malang. The culture of communication openness partially has a positive and significant effect on the willingness to report patient safety incident. Teamwork, staff composition, feedback and learning from previous errors, non-punitive response to error, management support, cooperation between teams, handover and patient transfer process does not affect the willingness of patients to report patient safety incident.